2020
DOI: 10.1002/cam4.2849
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA damage repair gene somatic mutations and immune‐related gene expression in ovarian cancer

Abstract: Background Defects in DNA damage repair (DDR) system may lead to genomic instability and manifest as increased immunogenicity. DDR deficiency is prevalent in ovarian cancer (OvCa); however, the association of DDR mutation with immune profiles in OvCa remains largely unknown. This knowledge will provide an essential basis to the rational design of biomarker‐guided immune combination therapy of OvCa in the future. Methods Whole‐exome sequencing data of 587 OvCa from The Cancer Genome Atlas (TCGA) were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
6
19
0
Order By: Relevance
“…Finally, we observed considerable differences in the deregulation of transcriptome for the same mutation when comparing breast and ovarian cancers. Consistent with previous reports BRCA mutations in breast cancer were mostly associated with regulation of cell cycle, DNA damage, and cell proliferation in breast cancer [71], and with immune system-related processes in ovarian cancer [61], which may be an indicator of differential role of BRCA1 and BRCA2 in the pathogenesis of these diseases. Previous studies have already suggested mechanisms of how DNA damage may trigger immune response [72,73]; however, the question of why its intensity is higher in ovarian rather than in breast cancer remains open.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we observed considerable differences in the deregulation of transcriptome for the same mutation when comparing breast and ovarian cancers. Consistent with previous reports BRCA mutations in breast cancer were mostly associated with regulation of cell cycle, DNA damage, and cell proliferation in breast cancer [71], and with immune system-related processes in ovarian cancer [61], which may be an indicator of differential role of BRCA1 and BRCA2 in the pathogenesis of these diseases. Previous studies have already suggested mechanisms of how DNA damage may trigger immune response [72,73]; however, the question of why its intensity is higher in ovarian rather than in breast cancer remains open.…”
Section: Discussionsupporting
confidence: 91%
“…It is tempting to speculate that the correlation of high GBP1 mRNA expression and better survival, could reflect an underlying anti-tumor T cell response. Indeed, a very recent study reported an association between somatic mutations of DNA damage repair genes and a specific immune signature, which included the GBP1 gene in EOC [43]. It is well established that defects in the DNA repair system are associated with increased mutational load and generation of tumor-associated neo-antigens, which enhance tumor immunogenicity and the potential responsiveness to immunotherapy [44].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, gene up-regulation in DDR pathways is associated with tumor metastasis (40). DDR gene mutations were linked to immune-related gene expression in ovarian cancer and muscle invasive bladder cancer (41,42). DDR was also reported to be involved in cancer metabolism.…”
Section: Discussionmentioning
confidence: 99%